Brain-to-blood efflux transport of endogenous compounds and its analogue drug at the blood-brain barrier - Terasaki, Tetsuya (Henry Stewart Talks, 2008)
The blood-brain barrier is not just a static wall, but "a cerebral clearance organ", The BBB multiple efflux transporters play a part in CNS detoxification by pumping out endogenous compounds from the brain, Neurotransmitters, Neuromodulators, Metabolites of neurotransmitters, Uremic toxins, Cholesterol metabolites
Archived at 2018/05/31